2018
DOI: 10.13031/trans.12470
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Energy Sorghum under Limited Irrigation Levels Using the EPIC Model

Abstract: Abstract. Energy sorghum is one of the most attractive alternatives for producing energy in many regions of the world because of the high biomass productivity obtained in a short period. However, it faces many challenges, particularly where water resources are limited. Crop simulation models are suitable decision support tools for the assessment of crop water use and biomass production under different spatial and climatic conditions. Calibration of simulation models to local conditions is a necessary procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
2
3
0
Order By: Relevance
“…The dry biomass productivities obtained at the Weslaco site are comparable to those reported by Chavez and Enciso [16], in which the energy sorghum was grown under similar conditions. They obtained productivities that ranged from 26.57 to 28.05 Mg ha −1 , which is similar to the ones observed by Rocateli and Raper [19], who reported dry biomass yields of 26.0 to 31.6 Mg ha −1 in a study conducted in the southeastern US, and the dry biomass reported by Palumbo and Vonella [20], who reported 20.9 to 26.4 Mg ha −1 in a Mediterranean environment.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The dry biomass productivities obtained at the Weslaco site are comparable to those reported by Chavez and Enciso [16], in which the energy sorghum was grown under similar conditions. They obtained productivities that ranged from 26.57 to 28.05 Mg ha −1 , which is similar to the ones observed by Rocateli and Raper [19], who reported dry biomass yields of 26.0 to 31.6 Mg ha −1 in a study conducted in the southeastern US, and the dry biomass reported by Palumbo and Vonella [20], who reported 20.9 to 26.4 Mg ha −1 in a Mediterranean environment.…”
Section: Discussionsupporting
confidence: 85%
“…The sorghum cultivars Blade ES 5140 and Blade ES 5200 reached maximum productivities of 25.2 and 28.7 Mg h −1 , respectively. These final dry biomasses performed as expected and were comparable with yields obtained in similar conditions in previous studies [16].…”
Section: Dry Biomasssupporting
confidence: 89%
“…Furthermore, EPIC is capable of predicting the effects of field management parameters, and their combined impact on crop yields for areas (Ko et al, 2009;Chavez et al, 2018;Yang et al, 2019;Feng et al, 2021). For example, simulating the variance of soil water and its effects on crop production.…”
Section: Irrigation Prejectionmentioning
confidence: 99%
“…Although conducting agronomic trials helps to identify suitable crop management practices under real‐world conditions, it requires considerable investment of time and other resources. Crop models work as tools to integrate information from agronomic experiments and facilitate prediction of varying spatial (e.g., land), temporal (e.g., weather), and management (e.g., irrigation, fertilizer, tillage) factors on crop growth and yield (Attia et al., 2016a; Chavez et al., 2018; Jones et al., 2003). Researchers have been increasingly using simulation models in applications such as prediction of yield, determination of optimal management practices, precision agriculture, and in many other aspects of agronomic and plant breeding activities around the globe (Adhikari et al., 2016; Attia et al., 2016a; Chen et al., 2017; Marin et al., 2012; Sannagoudar et al., 2019 Sonkar et al., 2019).…”
Section: Introductionmentioning
confidence: 99%